Bound magnetic polaron in Zn-rich cobalt-doped ZnSe nanowires. (5th January 2018) - Hou, Lipeng; Pan, Longfei; Liang, Bianbian; Liu, Yuting; Zhang, Li; Bukhtiar, Arfan; Shi, Lijie; Liu, Ruibin; Zou, Bingsuo
Abstract: The micro-luminescence spectra of the diluted magnetic semiconductor (DMS) can reflect the spin–exciton interaction and related relaxation process. Here the micro-photoluminescence (micro-PL) spectra and PL lifetime measurements have been done on an individual ferromagnetic (FM)-coupled cobalt (Co) doped zinc selenide (ZnSe) nanowire. There occurs a double-peak profile in its near bandedge emission spectrum: the first peak is from free exciton (FX) and the second comes from magnetic polaron (MP). In their temperature dependent PL spectra, the MP emission peak demonstrates obviously temperature-independent behavior, in contrast to the behaviors of FX and reported exciton MP in nanobelt. It is found that in this Co(II) doped ZnSe nanowires, this MP's temperature-independent emission is related to the coupling between exciton and a FM nanocluster (↑↑↓). The nanocluster is likely due to the interaction of Se vacancies of the wide bandgap semiconductors with the antiferromagnetic (AFM) arrangement transition metal (TM) ions in these Se-deficient Co doped ZnSe nanowires. These results reflect that the AFM coupling TM ions pair can give rise to FM behavior with the involvement of positive charge defect, also indicating that the micro-luminescence detection can be used to study the magnetic coupling in DMS.